Aggressive papillary tumor of endolymphatic sac: case report of a rare neoplasia - Eduardo Cambruzzi; Karla Lais Pêgas; Leandro P. Almeida; Gerson Evandro Perondi; Leandro I. Dini
ABSTRACT Aggressive papillary endolymphatic sac tumor (ELST) is a rare neoplasm, occasionally related to von Hippel-Lindau disease, characterized by locally aggressive growth with temporal bone destruction. The authors report a case of ELST in a female patient exhibiting fifth through eighth cranial nerve paralysis. Computed tomography (CT) revealed a large lytic process involving the right temporal bone. The patient underwent surgical resection. At microscopy, a neoplastic process was identified exhibiting monomorphic columnar cells with mild atypias, arranged in a papillary pattern. The lesion exhibited positivity for A31/AE3, epithelial membrane antigen (EMA), and vimentin; and negativity for synaptophysin, glial fibrillary acidic protein (GFAP), neuron-specific enolase (NSE), thyroglobulin, transthyretin, chromogranin, thyroid transcription factor 1 (TTF-1), trans-acting T-cell specific transcription factor GATA-3, and intestinal transcription factor CDX-2. The diagnosis of ELST was then established. Six years after surgical resection, lesion recurrence was observed.